Implementación de un sistema de control que permita sincronizar dos etapas de una máquina impresora de tapas plásticas. - Macías Liberio, Henry Geovanny (2019)
In the company Plásticos Ecuatorianos S.A. one of its printing machines has shortcomings that affect its productivity, this situation has motivated "Design a control system that synchronizes two stages of a printing machine, and, prevent the crushing and misplacing the printing of plastic lids". In its development, information has first been collected regarding the electrical and electronic elements of a synchronization control system; then the diagnosis is made of the situation of the printer for plastic caps installed in the company Plásticos Ecuatorianos, which shows that the system of synchronism is not adequate and presents a mismatch in the printing, which produces crushing of the lids, losses due to products not conform and for time in mechanical repairs. After analyzing various criteria, it was decided to replace the original mechanical system, by one that uses the principle of electronic synchronism, in this way the machinery meets the required movements, and every certain distance and makes a correct impression without damaging lids. In the project exploratory, explanatory and descriptive research was used; Exploratory when verifying documents of the machine to know its operation and establish what you want to perform to give a solution to the problem; explanatory to describe the causes behind the project, and descriptive to adequately communicate the research.